Home is where our journey begins – getting more patients home after a hip fracture with an orthopaedic supportive discharge team - Lisk, Radcliffe (Future Healthc J, 2017)
Hip fracture (neck of femur fracture (NOF)) patients spend a significant amount of time in hospitals, recuperating after the acute event and undergoing rehabilitation. This model of care increases the risk of institutionalisation and may lead to hospital-related harm. An orthopaedic supportive discharge team was set up using a £90,000 grant from the Ashford and St Peter’s NHS Foundation Trust’s Innovation Fund and care was improved using plan-do-study-act cycles. The team was operational from the 1 March 2014 with the capacity to support eight patients. Engagement meetings were held with patients, GPs and community partners. To reduce risk of readmission, patients were given fast track access to fracture and geriatric clinics. The team’s capacity increased to 12 patients through efficiency and introduction of cross-specialty working. The addition of a nurse and therapy assistant – coupled with further improvement in processes – increased capacity still further to 20 patients. In 2 years, 459 patients (211 NOFs) were referred to orthopaedic supportive discharge. Home-to-home discharges improved from 53.9% to 66.3% and length of stay reduced from 21.5 to 14.03 days, enabling a rehabilitation ward to be closed with significant cost savings for NOF patients. 99.6% of patients using orthopaedic supportive discharge provided positive feedback. Orthopaedic supportive discharge should be part of NOF services as it is cost effective, increases home-to-home discharges and reduces length of stay.